PESSIMISM IN JOJO MOYES' ME BEFORE YOU - Kinzi Rompas; Agustine C. Mamentu; Delli Sabudu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
Me Before You tells about a man named Will Traynor. He is a rich and successful man who loved all aspects of his life, until he lost control of his body due to a motorcycle accident. Things worsen after Will's ex-girlfriend, Alicia, and best friend Rupert reveal that they are getting married. The purpose of this research is to reveal about Pessimism in Jojo Moyes’ Me Before You. This research is categorized as a qualitative research in which the data are in the form of words. The data collection is categorized as primary and secondary sources. The primary source is the novel itself, and the secondary sources are other books and references that used support this research. The writer uses objective approach to analyze the data. The analysis shows the pessimism of Will as the main character in the novel. Pessimism starts to appear when he suffers a traffic accident that leaves him paralyzed in a wheelchair. He is a rich and successful man who loved all aspects of his life, and suddenly he lost control of his body because of the accident. It makes him being a pessimist